Understanding nonlinear molecular responses in highly inhomogeneous electric fields: Insights from imidazole and pyrrole - Quinteiro, Guillermo Federico (2025)
The study of molecules subjected to highly inhomogeneous electric fields, whether static or time-dependent, is relatively unexplored. Advances in this area, as shown in condensed matter physics, could lead to new insights into molecular physics and offer novel ways to control molecules, driving technological innovations. In this work, we numerically investigate the properties of imidazole and pyrrole under the influence of highly inhomogeneous static and dynamic electric fields, modeled by a new procedure employing charge configurations, using density functional theory calculations with the DALTON software package. We analyze their dipole moments, highest occupied molecular orbital–lowest unoccupied molecular orbital gap energies, polarizability, and first and second hyperpolarizabilities across different field orientations. Our results show that inhomogeneous fields acting upon the molecule would induce changes in nonlinear optical properties, with the response depending on the nature of the inhomogeneity. These findings are relevant for fundamental research and practical applications. Tailored electric non-uniform fields can help unveil complex relationships among molecular orbitals that induce specific nonlinear optical phenomena. Moreover, they can enhance or suppress nonlinear responses, opening up new avenues for molecular engineering and device design.